Relationship Between Profile Characteristics and Knowledge Level of State Agricultural University (SAU) and Farmers Practice (FP) Respondents on Nutrient Management in Rice (Indian Journal of Extension Education, 2017)
Relationship between profile characteristics and knowledge level of state agricultural university (SAU) and farmers practice (FP) respondents on nutrient management in rice in Nalgonda district of Telangana state need probing. The data was collected from 90 respondents randomly representing 15 villages of Three mandals during the year 2015 using structured interview schedule. The findings revealed that the independent variables viz. farm size, farming experience, irrigation water supply, extension contact, capacity enhancement activities exhibited positive and significant relationship at five per cent level of significance whereas education, information seeking behaviour exhibited positive and significant relationship at one per cent level of significance whereas age, annual income, machinery ownership, profit oriented behaviour exhibited non-significant relationship with knowledge level of SAU respondents. With respect to FP respondents variables like education, annual income, farm size, extension contact, capacity enhancement activities exhibited positive and significant relationship at five per cent level of significance whereas age farming experience, irrigation water supply, information seeking behaviour, machinery ownership, profit oriented behaviour exhibited non significant relationship with knowledge level of FPrespondents.